2013
DOI: 10.1172/jci67871
|View full text |Cite
|
Sign up to set email alerts
|

Hematopoietic stem cells are acutely sensitive to Acd shelterin gene inactivation

Abstract: The shelterin complex plays dual functions in telomere homeostasis by recruiting telomerase and preventing the activation of a DNA damage response at telomeric ends. Somatic stem cells require telomerase activity, as evidenced by progressive stem cell loss leading to bone marrow failure in hereditary dyskeratosis congenita. Recent work demonstrates that dyskeratosis congenita can also arise from mutations in specific shelterin genes, although little is known about shelterin functions in somatic stem cells. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 66 publications
(110 reference statements)
2
23
0
Order By: Relevance
“…homozygous for the acd allele are profoundly defective in transplantation assays, and complete inactivation of Tpp1 results in severe depletion of hematopoietic progenitors (Jones et al 2014). Deletion of Tpp1 in the epithelial tissue leads to perinatal death, severe skin hyperpigmentation, defective hair follicle morphogenesis, and epithelial dysplasia (Tejera et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…homozygous for the acd allele are profoundly defective in transplantation assays, and complete inactivation of Tpp1 results in severe depletion of hematopoietic progenitors (Jones et al 2014). Deletion of Tpp1 in the epithelial tissue leads to perinatal death, severe skin hyperpigmentation, defective hair follicle morphogenesis, and epithelial dysplasia (Tejera et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, patients with dyskeratosis congenita have mutations in the DKC1 gene, an important component of the telomerase complex 191 . Defects in telomere maintainance lead to deprotection of telomeres and, in HSCs, cause failure to sustain bone marrow reconstituting activity 192 .…”
Section: Dna Damage In Aging Stem Cellsmentioning
confidence: 99%
“…We recently demonstrated that Acd critically regulates HSC homeostasis (39). In mice with hypomorphic acd alleles, we observed G2/M arrest in fetal hematopoietic progenitors.…”
Section: Tin2mentioning
confidence: 66%
“…This profound in vivo significance is most prevalent in tissues that require active turnover and robust stem cell compartments, such as hematopoietic tissues. In addition to developmental defects, several mouse models of shelterin dysfunction revealed features reminiscent of the human syndrome dyskeratosis congenita (35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45).…”
Section: Pot1mentioning
confidence: 99%